Optimalisasi Penguatan Basis Ke-Dkm-An Guna Mencegah Paham Radikalisme Di Desa Wisata - Aang Andi Kuswandi; Anwar Purnawijaya; Bela Safitri; Burhanudin Burhanudin; Daris Susanto; Rina Marliani; Siti Nurhalipah; Yayat Hidayat (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
In Kertayasa Village there are several things that are starting to disappear from the activites usually carried out in the mosque, such as worship rituals which are carried out in congregation, religious activites and even religious education that is starting to fade. The lack of community participation in managing the prosperity of mosques in this village is caused by the management’s low knowledge of the applicable mechanisms and regulations, so that the community’s social concern for ukhuwah Islamiyah begins to decline. With this happening, because Kertayasa village is a tourist village, there is also concern. Understand, intolerance and even radicalism enter through this gap. Through public dialogue activites, optimalization of strengthening the base of the mosque prosperity council to prevent radicalism in tourist village. By providing guidance to mosque managers and providing insight into intolerance and radicalism so that mosque managers and society in general can screen for the possibility of such crimes occurring. In carrying out thus public dialogue, the mosque properity council in each hamlet and the communities involved have gained knowledge about preventing radicalism through increasing national insight, the causes of radicalism/terrorism, the legal basis for eradicating terrorism in Indonesia and efforts to improve the performance of mosque management. With this, the community at least has the provisions to recognize and prepare themselves both in strengthening mosque management and in countering ideas that are contrary to Islamic teachings